Implementation of merdeka curriculum by Islamic religious education teachers at junior high school - Pratiwi, Rizky Indah; Iman Firmansyah, Mokh.; Subakti, Ganjar Eka (UIN Salatiga, 2024)
This research aims to see firsthand how the implementation of Merdeka Curriculum is carried out by Islamic Religious Education teachers at SMPN 7 Bandung, as one of the driving schools as well as the first school at the junior high school level to implement Merdeka Curriculum. Using a qualitative approach and a case study method at SMPN 7 Bandung, which was explored through interviews with three Islamic Religious Education teachers there, the results of this study were then analyzed through the stages of data reduction, data presentation, and conclusion drawing, so this study resulted So this study resulted in the conclusion that the implementation of the Merdeka Curriculum by Islamic Religious Education teachers at SMPN 7 Bandung is in accordance with the targets and objectives to be achieved, both by the Islamic Religious Education teachers themselves, by the school, and by the government that formulated the Merdeka Curriculum. This research has implications for the importance of planning the implementation of the Independent Curriculum by analyzing various indicators that influence it. From these implications, this research contributes significantly to finding the fact that careful planning in a curriculum implementation will help Islamic Religious Education teachers in carrying out learning better